2000
DOI: 10.1590/s0100-879x2000001200014
|View full text |Cite
|
Sign up to set email alerts
|

Acute AT1 receptor blockade does not improve the depressed baroreflex in rats with chronic renal hypertension

Abstract: To assess the role of angiotensin II in the sensitivity of the baroreflex control of heart rate (HR) in normotensive rats (N = 6) and chronically hypertensive rats (1K1C, 2 months, N = 7), reflex changes of HR were evaluated before and after (15 min) the administration of a selective angiotensin II receptor antagonist (losartan, 10 mg/kg, iv). Baseline values of mean arterial pressure (MAP) were higher in hypertensive rats (195 ± 6 mmHg) than in normotensive rats (110 ± 2 mmHg). Losartan administration promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The first is the operating point of the reflex (i.e., arterial pressure) and the second is the sensitivity of the reflex . The operating point and the sensitivity of the baroreceptor reflex are altered in physiological and pathophysiological situations, such as development , aging , pregnancy , different sleep states , or hypertension . Activation of baroreceptors results in increased firing of action potentials, with the rapidity determined by the degree of mechanical stretch.…”
Section: The Baroreceptor Reflexmentioning
confidence: 99%
“…The first is the operating point of the reflex (i.e., arterial pressure) and the second is the sensitivity of the reflex . The operating point and the sensitivity of the baroreceptor reflex are altered in physiological and pathophysiological situations, such as development , aging , pregnancy , different sleep states , or hypertension . Activation of baroreceptors results in increased firing of action potentials, with the rapidity determined by the degree of mechanical stretch.…”
Section: The Baroreceptor Reflexmentioning
confidence: 99%
“…In the present study, AT1 blockade was not applied to 1K1C animals because of the risk of kidney failure. Previous ultra-short term studies with losartan have not shown an improved baroreflex function in this volume-dependent model of renovascular hypertension (1K1C) [43]. …”
Section: Discussionmentioning
confidence: 90%
“…Although GCIP-27could lower blood pressure in spontaneously hypertensive rats, the hypotensive effect of GCIP-27 is significant weaker than that of losartan. And due to compensation, the normotensive animals, such as rats, dogs and patients, are less sensitive to hypotensive agents, such as losartan and nitroprusside, etc., than hypertensive subjects [ 32 , 33 ]. We have also ever observed that GCIP-27 had no influence on the blood pressure in normotensive rats [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%